A taxonomy of masculinities in Frances Trollope's Domestic Manners of the Americans (1832) and Anthony Trollope's North America (1862). Issue 4 (2nd October 2019) - Lewis, Daniel
ABSTRACT: This essay examines how North American models of masculinity are defined, compared, and occasionally endorsed in Frances Trollope's Domestic Manners of the Americans (1832) and Anthony Trollope's North America (1862). In addition, the article explores how those models relate to American, Canadian, and British national identity in the mid-to-late nineteenth-century. The article's examination of these taxonomies of masculinities shows how they reacted and contributed to changing ideals about masculine gender identities. These ideals are, to quote Mary Poovey, "both contested and always under construction […] always in the making" (1988, 3), and this article illustrates how the Trollopes helped construct and challenge these ideas about men.